Identification of Fire Disaster Vulnerability in Karang Rejo Sub-District, Balikpapan Central District - Dwiana Novianti Tufail; Hade Satrianas Neowa; Amiruddin Akbar Fisu (PENA TEKNIK: Jurnal Ilmiah Ilmu-Ilmu Teknik, 2023)
At least 617 cases of fire disasters were recorded in Balikpapan City from 2010 to 2020. In response, fire disaster mitigation is still a problem, especially in dense residential areas and unclean environments. One of the sub-districts with the characteristics of dense settlements and a history of fire incidents is Karang Rejo Village. This condition can be an obstacle in disaster mitigation. Therefore, it is necessary to identify appropriate mitigation efforts for this sub-district. Vulnerability assessment can be an essential first step to reducing the impact and losses of a fire disaster. The purpose of this study is to formulate fire disaster mitigation based on the level of vulnerability in Karang Rejo Village, Central Balikpapan District, using the spatial multi-criteria analysis method. The research results obtained are structural fire disaster mitigation at low, medium, and high vulnerability by mitigating aspects of building density, percentage of built-up areas, building materials, the width of access roads, availability of water reservoirs, availability of vacant land, the portion of households working in the informal sector, and the ratio of poor people.